Identifying learning pace in mathematics classrooms: What teachers can see—and what they miss without information support - Pujia Siti Balkist; Farhan Hamdallah; Krida Singgih Kuncoro; Rizky Dwi Siswanto; Dadan Rahmat (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Identifying students’ learning pace is a central task for teachers in inclusive mathematics classrooms, yet such identification is often based on observable performance indicators such as task completion speed and correctness of answers. This study investigates the extent to which teachers’ judgments of students’ learning pace align with students’ number sense profiles, and examines which aspects of number sense remain invisible without information support. Using a descriptive–comparative design situated in the analysis phase of design research, the study involved an inclusive lower secondary mathematics classroom. Teachers classified students as slow, moderate, or fast learners based on regular classroom observations, while students completed a validated number sense assessment focusing on estimation, numerical magnitude understanding, strategy flexibility, and evaluation of reasonableness. The results reveal partial alignment between teachers’ judgments and students’ number sense, with systematic misalignments among students categorized as fast and slow learners. Some fast learners demonstrated procedural fluency without adequate evaluation of reasonableness, while some slow learners exhibited emerging number sense that was not reflected in teachers’ judgments. The findings highlight the need for information support to make latent cognitive indicators visible and support more equitable learning pace identification. By reframing learning pace as a cognitively informed construct rather than a purely performance-based label, this study contributes empirical grounding for the design of information-supported systems that augment teacher judgment and promote inclusive assessment practices in mathematics education.